ANALISIS HUBUNGAN GENDER TERHADAP PREFERENSI E-COMMERCE DAN PEMBELIAN KONVENSIONAL DI KALANGAN MAHASISWA FEBI UINSU - Nabila Keysha Mutmainah; Dwi Septianingrum; Nurul Hidayah; Anggi Safitri Lubis; Siti Suaibah Nasution (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
The shift in digital technology has changed the behavior of consumers, including college students, in choosing purchasing channels that suit their needs and convenience. This study aims to analyze the relationship between gender and student purchasing preferences, both through E-commerce and conventional purchases. The sample of this study is 40 students of the Faculty of Islamic Economics and Business UINSU. The method used is the Chi-Square test with a quantitative approach. The results of the study showed that gender did not have a significant influence on students' spending preferences. Despite the difference in the number of male and female respondents who choose between conventional or e-commerce purchases, the Chi-Square test results with a significance value of 0.944 show no significant relationship between gender and shopping preferences. Thus, students' purchasing decisions are more of an individual choice, not influenced by gender.